(untitled) (PRÁXIS EM SAÚDE, 2025)
The present study aims to analyze the therapeutic effects of ayahuasca on mental health through an integrative review. For this purpose, articles published in the last ten years were collected from the PubMed, Scopus, and Google Scholar databases, using the descriptors “ayahuasca,” “depression,” “anxiety,” and “mental health.” After examining 96 captured works, 18 empirical studies were selected that investigated the therapeutic potential of ayahuasca in psychiatric disorders. The results indicate that ayahuasca exhibits antidepressant, anxiolytic, and cognitive properties, as well as being associated with improvements in quality of life. Most of the reviewed studies suggest that its effects are related to the modulation of serotonergic receptors and the ritualistic context in which it is used. Despite these promising findings, further research is needed to evaluate the long-term safety and efficacy of the substance, as well as the development of guidelines for its controlled therapeutic use.